Special Rules Governing the Rights of the Parties to the Results of Scientific and Technical Activities Obtained in the Performance of Research, Development and Technological Works at the Expense of the Russian Federation - S. A. Bikmetova (Теоретическая и прикладная юриспруденция)
The article analyzes the special rules governing the legal relations between state customers and contractors on the distribution of the rights of the parties to the results of scientific and technical activities obtained in the performance of research, development and technological works at the expense of the Russian Federation. It is shown that in General, the evolution of the regulatory framework in this area has both positive and negative trends. Conclusions are drawn that the system of legal regulation of legal relations concerning distribution of the rights to the results of scientific and technical activity received at performance of research, developmental and technological works at the expense of the Russian Federation, developing, being improved, is still in a formation stage, it cannot be considered complete.